Kicking You When You're Already Down: The Multipronged Impact of Austerity on Crime - Giulietti, Corrado (2020)
The UK Welfare Reform Act 2012 imposed a series of welfare cuts, which disproportionately impacted ex-ante poorer areas. In this paper, we consider the impact of these austerity measures on two different but complementary elements of crime -- the crime rate and the less-studied concentration of crime -- over the period 2011-2015 in England and Wales, and document four new facts. First, areas more exposed to the welfare reforms experience increased levels of crime, an effect driven by a rise in violent crime. Second, both violent and property crime become more concentrated within an area due to the welfare reforms. Third, it is ex-ante more deprived neighborhoods that bear the brunt of the crime increases over this period. Fourth, we find no evidence that the welfare reforms increased recidivism, suggesting that the changes in crime we find are likely driven by new criminals. Combining these results, we document unambiguous evidence of a negative spillover of the welfare reforms at the heart of the UK government's austerity program on social welfare, which reinforced the direct inequality-worsening effect of this program. More deprived districts are more exposed to the welfare reforms, and it is these districts that then experience the further negative consequences of the reforms via increased crime. Our findings underscore the importance of considering both multiple dimensions of crime as well as considering different levels of spatial aggregation of crime data. Given that it is violent crime that responds to the (economically-based) welfare cuts, our work also highlights the need to develop better economic models of non-rational crime.Comment: draft 1.